THE BIG FIVE PERSONALITY: AGREEABLENESS, CONSCIENTIOUSNESS, EXTROVERSION, NEUROTICISM, OPENNESS TO EXPERIENCE TERHADAP IMPULSIVE BUYING BEHAVIOR PADA E-COMMERCE GEN Z SURABAYA - Esti Purwaningtyas; Laily Muzdalifah; Muhafidhah Novie; Afifatus Sholikhah (JURNAL LENTERA BISNIS, 2025)
Impulsive buying behavior in e-commerce is increasing among Generation Z, especially in Surabaya. This study aims to analyze the influence of Big Five Personality : Agreeableness, conscientiousness, extroversion, neuroticism, and openness to experience on impulsive behavior in online shopping. This study involved 170 Generation Z e-commerce users from Surabaya, using a quantitative purposive sampling approach. The study shows that agreeableness and neuroticism have a significant positive effect on impulsive buying, while conscientiousness has a negative impact. Meanwhile, extroversion and openness to experience do not show a significant effect on impulsive buying behavior. The results indicate that personality plays an important role in determining the tendency to make impulsive purchases in e-commerce.